Analisis SWOT Terhadap Strategi Pemasaran Layanan SAP Express pada PT. SAP - Elyarni, Reca; Hermanto, Hermanto (Metris: Jurnal Sains dan Teknologi, 2016)
The purpose of the study is to determine the internal factors (IFAS) and external factors (EFAS) and a marketing strategy by using SWOT method. The observation and interviews are applied to solve the existing problems and to improve marketing strategies in PT SAP. In order to determine a marketing strategy, the company: (a) put through questionnaires with the statement that has been made from observations and interviews and get 24 statements to all factors, (b) calculate the results of SWOT analysis in order to get score on a quantitative strategy planning matrix combination. The results show that the marketing strategy should be implemented at the company are: to take advantage of its strategic location, has its own building to get potential customers, providing an affordable price, to establish good relations with partners, as well as adding branches.